Goldhillite, Cu5Zn(AsO4)2(OH)6⋅H2O, a new mineral species, and redefinition of philipsburgite, Cu5Zn[(AsO4)(PO4)](OH)6⋅H2O, as an As–P ordered species. (13th June 2022) - Ismagilova, Rezeda M.; Rieck, Branko; Kampf, Anthony R.; Giester, Gerald; Zhitova, Elena S.; Lengauer, Christian L.; Krivovichev, Sergey V.; Zolotarev, Andrey A.; Ciesielczuk, Justyna; Mikhailova, Julia A.; Belakovsky, Dmitry I.; Bocharov, Vladimir N.; et al.
Abstract: Philipsburgite has been redefined as the intermediate member of the goldhillite–philipsburgite–kipushite isomorphous series with the ideal formula Cu5 Zn[(AsO4 )(PO4 )](OH)6 ⋅H2 O due to the site-selective As–P substitution. The new mineral goldhillite, ideally Cu5 Zn(AsO4 )2 (OH)6 ⋅H2 O [or Cu5 Zn(AsO4 )(AsO4 )(OH)6 ⋅H2 O], is the arsenate end-member of this series. Goldhillite occurs on fracture surfaces in a rock comprised mostly of quartz with iron hydroxides in association with mixite, cornwallite and conichalcite. Goldhillite forms transparent, bright emerald-green, tabular crystals with vitreous lustre, flattened on 100, up to 1 mm across and in rosettes up to 1.5 mm. The mineral is brittle with uneven fracture and perfect cleavage on 100; the Mohs hardness is 3.5. The calculated density for the holotype is 4.199 g cm –3 . The Raman spectrum is consistent with the presence of H2 O-molecules, OH-groups, AsO4 tetrahedra and traces of PO4 . Electron microprobe analyses of goldhillite (H2 O content based on the crystal structure) provided: CuO 48.91, ZnO 13.18, As2 O5 26.06, P2 O5 3.25, H2 O 8.97, total 100.37 wt.%. The empirical formula for goldhillite based on O = 15 apfu is (Cu4.69 Zn1.23 )Σ5.92 (As0.86 P0.18 O4 )2 (OH)5.61 ⋅H2 O. The crystal structures of goldhillite and philipsburgite were determined using single-crystal X-ray diffraction data and refined to R 1 = 0.054 (for 2365 I > 2σ I reflections) and 0.052 (for 2308 I > 2σ I reflections), respectively. Goldhillite is monoclinic, P 21 / c, a = 12.3573(5), b = 9.2325(3), c = 10.7163(4) Å, β = 97.346(4)°, V = 1212.59(8) Å 3 and Z = 4. Philipsburgite is monoclinic, P 21 / c, a = 12.3095(9), b = 9.2276(3), c = 10.7195(3) Å, β = 97.137(7)°, V = 1208.16(10) Å 3 and Z = 4. The strongest lines of the powder X-ray diffraction pattern of goldhillite [ d, Å ( I, %)( hkl )] are: 4.09 (28)(300), 3.41 (23)(122, 221, 311), 2.57 (100)(132, 114, 204 ), 2.17 (18)(423, 332), 1.95 (22)(432) and 1.54 (20)(136, 060). Goldhillite is named after its type locality, the Gold Hill mine, Tooele County, Utah, USA.